2017
DOI: 10.1002/advs.201700608
|View full text |Cite
|
Sign up to set email alerts
|

Electroplex as a New Concept of Universal Host for Improved Efficiency and Lifetime in Red, Yellow, Green, and Blue Phosphorescent Organic Light‐Emitting Diodes

Abstract: A new concept of host, electroplex host, is developed for high efficiency and long lifetime phosphorescent organic light‐emitting diodes by mixing two host materials generating an electroplex under an electric field. A carbazole‐type host and a triazine‐type host are selected as the host materials to form the electroplex host. The electroplex host is found to induce light emission through an energy transfer process rather than charge trapping, and universally improves the lifetime of red, yellow, green, and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…According to the previous results reported in literatures [22,28,40], the newly formed peaks in EL spectra were possibly related to phosphorous emission, exciplex emission, or/and electroplex emission. As the shoulder peak could not be observed in the PL spectrum of the solid film, it should not be caused by phosphorous emission [40].…”
Section: Energy Levels and Theoreticsupporting
confidence: 69%
See 2 more Smart Citations
“…According to the previous results reported in literatures [22,28,40], the newly formed peaks in EL spectra were possibly related to phosphorous emission, exciplex emission, or/and electroplex emission. As the shoulder peak could not be observed in the PL spectrum of the solid film, it should not be caused by phosphorous emission [40].…”
Section: Energy Levels and Theoreticsupporting
confidence: 69%
“…This procedure produces the CT configuration, accompanied with the electroplex emission [42]. In Song et al's case [28], the LUMO gap between 3,3-di(9H-carbazol-9-yl)biphenyl (mCBP) and 2,8-bis(4,6-diphenyl-1,3,5-triazin-2-yl)dibenzo[b,d]furan (DBFTrz) was around 0.5 eV. However, here, for 3Ph-Cz-CN and TPBi, the electron at the LUMO of TPBi could directly cross recombine with the holes at the HOMO of 3Ph-Cz-CN even though the LUMO gap was just 0.3 eV.…”
Section: Energy Levels and Theoreticmentioning
confidence: 98%
See 1 more Smart Citation
“…This will minimize the degradation of the devices by avoiding the decomposition of host materials in the emitting layer, extending the lifetime of the OLEDs. Moreover, the upconversion process occurring in the TADF‐type exciplex host will reduce the excited state lifetime of triplet excitons in the host compared to that occurring in a non‐TADF type host; this is helpful to improve the lifetime of the devices …”
Section: Lifetime Improvement Of Oleds By Tadf Hostsmentioning
confidence: 99%
“…Previous studies have found that device lifetime can be enhanced by maximizing the RZ width . In conventional mixed‐ and graded‐EML devices, electron‐ and hole‐transporting hosts are mixed to achieve high charge balance and a wide RZ . The absolute position of the RZ is also important, as proximity to a transport layer interface can exacerbate degradation, or influence exciton confinement and charge balance .…”
Section: Introductionmentioning
confidence: 99%